Analisis Total Harmonic Distortion Terhadap Penambahan Filter Aktif Pada Modified Buck-Boost Inverter Untuk Mengurangi Common Mode Voltage Pada Motor Induksi - M, I Gede Mahardika; Pratama, I Putu Indra; Manuaba, Ida Bagus Gede; Partha, Cokorde Gede Indra; Wijaya, I Wayan Arta (Jurnal Ilmiah Wahana Pendidikan, 2024)
Buck-boost inverter is one tool that can convert Direct Current (DC) voltage into Alternating Current (AC) voltage while simultaneously increasing and decreasing the output voltage. On the other hand, there is a problem with induction motors, namely the presence of Common Mode Voltage (CMV) or the voltage between the neutral point of the motor and ground which can accelerate wear on the bearings and damage to the motor. One method that can reduce CMV is by using an active filter. Another problem due to the use of inverters is that there are harmonics due to the switching process. This research will examine the effect of adding modified BBI plus an active filter to a three-phase induction motor on CMV and THDv. This research process begins with designing a circuit simulation in the MATLAB application, then simulation testing is carried out to see its effect on CMV and THDv values. BBI simulation test results after the addition of active filters with conventional inverter circuit CMV worth 250V with THD worth 6744.45%, while the BBI circuit coupled with active filters worth 22V and THDv worth 114.53%. As well as the BBI circuit plus an active filter, CMV is worth 2.6V with THDv worth 65.30%.